Philosophical friendship between Brazil and Chile - Acevedo, Jorge; Aurélio Werle, Marco (Aoristo - International Journal of Phenomenology, Hermeneutics and Metaphysics, 2022)
One can expect a scientific journal to fulfill the purpose of disseminating research results, spreading works and new ideas and, now more than ever, franking space for the fruitful exchange among institutions under the dictum of the knowledge’s internationalization. Honoring its commitment as an academical philosophy journal, the present issue of the Aoristo - International Journal of Phenomenology, Hermeneutics and Metaphysics assumes the three afore mentioned missions, with emphasis on the last one.